Application of Remote Sensing for Mapping Soil Organic Matter Content - Sukojo, Bangun Muljo; Wahono, Wahono (Makara Journal of Technology, 2002)
Application of Remote Sensing for Mapping Soil Organic Matter Content. Information organic content is important in monitoring and managing the environment as well as doing agricultural production activities. This research tried to map soil organic content in Malang using remote sensing technology. The research uses 6 bands of data captured by Landsat TM (Thematic Mapper) satellite (band 1, 2, 3, 4, 5, 7). The research focuses on pixels having Normalized Difference Soil Index (NDSI) more than 0.3. Ground-truth data were collected by analysing organic content of soil samples using Black-Walkey method. The result of analysis shows that digital number of original satellite image can be used to predict soil organic matter content. The implementation of regression equation in predicting soil organic content shows that 63.18% of research area contains of organic in a moderate category.